SHM_415339_HST_3D Polygonal Stone Axe - Qallaki, Ylber; Strandberg, Caroline; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of an Early Neolithic polygonal stone axe collected in Sweden in 1858 and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=706

Link to Sök I Samlingarna

https://samlingar.shm.se/object/0FB1414D-680D-49B1-94E5-A993A5DE4BB0
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Swedish Early Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi